Peer Coaching Model To improve the competence of PAUD teachers in applying Scientific Learning - Sinaga, Lenni Arta F S; Nasrun, Nasrun; Mudjisusatyo, Yuniarto (CV. Inara, 2022)
Teachers have a role that determines the success of learning, including in early childhood education (PAUD). Scientific learning is one of the recommended approaches in PAUD, but the competence of teachers in implementing it is still low even though they have attended various related trainings. Peer coaching is one of the professional development models inherent in the work of teachers, but teachers need to be prepared to apply it consistently and sustainably. The peer coaching model developed prepares teachers in a series of collaborations with fellow teachers starting from determining focus, making observations, reflecting on observations, providing inspiring feedback and actively making improvements and strengthening so as to ensure the continuity of the professional development of PAUD teachers. From the results of the development and internal testing of the model, it is proven that the model is feasible to be applied. The results of field trials also prove that the peer coaching model is effective in increasing the competence of PAUD teachers in implementing scientific learning through the three stages of the peer coaching cycle.